Phonetic Accord in the Prophetic Hadeeth: A Descriptive study - Ahmed, Mustafa kamel (Al-Adab Journal, 2020)
This research aims to explore the applications of the Phonetic Accord phenomenon in the language of the Prophetic Hadeeth and explain some of its representations. It also explains the significance of using this phenomenon in the interpretation and direction of the Prophetic Hadeeth, which seemingly looks like a digression of the common Arabic language standards.